Responses in sediment phosphorus and lanthanum concentrations and composition across 10 lakes following applications of lanthanum modified bentonite. (15th June 2016) - Dithmer, Line; Nielsen, Ulla Gro; Lürling, Miquel; Spears, Bryan M.; Yasseri, Said; Lundberg, Daniel; Moore, Alanna; Jensen, Nicholai D.; Reitzel, Kasper
Abstract: A combined field and laboratory scale study of 10 European lakes treated between 2006 and 2013 with a lanthanum (La) modified bentonite (LMB) to control sediment phosphorus (P) release was conducted. The study followed the responses in sediment characteristics including La and P fractions and binding forms, P adsorption capacity of discrete sediment layers, and pore water P concentrations. Lanthanum phosphate mineral phases were confirmed by solid state 31 P MAS NMR and LIII EXAFS spectroscopy. Rhabdophane (LaPO4 · nH2 O) was the major phase although indications of monazite (LaPO4 ) formation were also reported, in the earliest treated lake. Molar ratios between La and P in the sediments were generally above 1, demonstrating excess La relative to P. Lanthanum was vertically mixed in the sediment down to a depth of 10 cm for eight of the ten lakes, and recovery of La in excess of 100% of the theoretical aerial load indicated translocation of the LMB towards the deepest areas of the lakes. Lanthanum was generally recovered from bed sediment samples following sequential chemical extraction from the HCl fraction. Soluble reactive P (SRP) release experiments on intact sediment cores indicated conditions of P retention (with the exception of two lakes) by sediments, indicating effective control of sediment P release, i.e. between two and nine years after treatment. Highlights: Soluble reactive P (SRP) was sequestered as rhabdophane in ten lanthanum modified bentonite (LMB) treated European lakes. SRP efflux from sediment in sediment cores was suppressed in 8 out of ten lakes at time of sampling. LMB was focused to the deepest areas of the lakes, and mixed more than ten cm into the sediment. Not all added La was involved in SRP binding. Confounding factors such as DOC could be responsible for the lower than expected La phosphate formation.